Volatile Profile in Different Aerial Parts of Two Caper Cultivars (Capparis spinosa L.) - Mar Grimalt; Lucía Sánchez-Rodríguez; Francisca Hernández; Pilar Legua; Ángel A. Carbonell-Barrachina; María S. Almansa; Asunción Amorós (Journal of Food Quality)
This research presents, for the first time, full volatile profiles of four aerial parts of caper plants (Capparis spinosa L.) from southeastern Spain. Volatile compounds in caper leaves and stems (together), flowers, flower buds, and fruits from two cultivars were identified and quantified using headspace-solid phase microextraction (HS-SPME) and gas chromatography with a mass spectrometry detector (GC-MS). Forty-three volatile compounds were identified in the caper shoots, 32 in caper flowers, with only 18, 10, and 6 compounds being found in flower buds, leaves, and fruits, respectively. The predominant compound in all studied materials was methyl isothiocyanate, with nerolidol, trans-2-hexenal, and nonanal playing key roles in flowers, leaves, and flowers buds, respectively. The two studied cultivars had the same volatile compounds but at very different concentrations, although the two studied cultivars are cultivated under the same climatic and agronomic conditions. Additionally, the predominant compounds, especially methyl isothiocyanate (6882 mg·kg−1 fw in flower buds of ORI 3 cultivar), can be separated and concentrated for future applications in food technology.